‘Sembur’ culture: Local wisdom in care of pregnant mother with malaria in Kupang (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
Malaria is one of the main public health problems in the province of East Nusa Tenggara (NTT). NTT currently ranks second in malaria cases in Indonesia after Papua. Pregnant women are a risk group, data show that pregnant women suffering from malaria complications in Kupang District is still very high due to the delay in treatment since many patients dominate the primary care of the traditional healer compared to health services. The traditional healers use herbs that are sprayed (sembur)to the patient. This action is an alternative treatment carried out by the local community because it is far from health facilities. Therefore, this study aims to determine the picture of semburculture in pregnant women suffering from malaria in Kupang Regency. This study uses qualitative techniques with a phenomenological approach. The informants were chosen by using purposive sampling and snowball approach. There were six informants, all of whom came from Kupang Regency. The data collected through depth interviews and field notes. Processing and analyzing data in the form of interview results are converted into verbatim transcripts and the results of field notes are analysed in the form of transcripts. The results of this study show three themes from all participants; (1) health beliefs and practices; (2) thoughts and feelings when conducting a sembur culture; (3) hope for a future life. This research is beneficial for maternal and child health as well as educational and service institutions.
Keywords: Malaria; sembur culture; pregnant mother; local wisdom.